Trajectories of change and relationship between parent-adolescent school-related conflict and academic achievement in early adolescence - Brković, Irma; Keresteš, Gordana; Puklek Levpušček, Melita (2014)
The study explored changes in parent-adolescent school-related conflict and academic performance over a five-year period among Croatian early adolescents and gender differences in these changes. We also examined the relationship between conflict and achievement. The study was performed by applying an accelerated approach to overlapping cohort design in which 851 adolescents (51.4% girls) and 1288 parents (53.9% mothers) took part in total, and the data were collected three times, approximately one year apart. Parallel forms of the Parent-Adolescent Conflict Scale were administered to measure parent-adolescent conflict in different dyads and from different informants. The results of the multilevel modeling showed an overall increase in parent-adolescent school- related conflict and the decrease in academic achievement. Boys showed a steeper increase in the frequency of school-related conflicts with parents and a steeper decrease in academic achievement than girls. Finally, a bidirectional link between school-related conflicts and academic achievement was confirmed.
Projekt MZOS